The Influence of Job Satisfaction on Employment Loyalty in Foreign Capital Companies (PMA) in the Manufacturing Sector in Bogor City - Chaidar, Diar Fachmi Rachmat (PT Aksara Indo Rajawali, 2023)
It is estimated that many employees who are dissatisfied with the service they receive at their workplace will have a negative impact on the progress of their company. So, we have to see whether job satisfaction has a big influence. This study will investigate whether job satisfaction has an impact on company work loyalty in foreign capital companies in the Bogor manufacturing sector. The research collected data using a qualitative descriptive approach. The research results show that the job satisfaction variable influences work loyalty in Foreign Capital Companies (PMA) in the manufacturing sector in the cities of Bogor with a significant level of 71.2%. Therefore, the results show that the job satisfaction variable influences work loyalty.